Análise dos fatores de risco associados a mortalidade de pacientes com comorbidades hospitalizados com Covid 19 no alto sertão da Paraiba - Nascimento, Silvana Gomes da Silva (2022)
The current COVID-19 pandemic is an international public health problem, given the conse-quences generated by its existence in terms of increased rates of morbidity, mortality, collapse in health services, unemployment, economic instability, among other factors. Faced with this scenario, we are faced with a challenge to be faced, identifying and establishing care for patients with comorbidities who are infected by Covid 19 and who most often develop complications and progress to death. Therefore, the present study aims to identify and evaluate the impact of risk factors and comorbidities associated with mortality of patients hospitalized with Covid 19 in Alto Sertão Paraibano. This is an exploratory, descriptive and analytical study. The research consisted of secondary data extracted from the Epidemiological Surveillance Information Sys-tem database through OpenDataSUS of the municipalities under study, from March 2020 to August 2021. database, has 83 variables and variables that were not of interest to the study were excluded from the sample. In the analysis of the data, descriptive statistics techniques were used, aiming to describe and summarize the information, in order to have a broader view of the variation of these values and to have a basis to explain the evolution of the cases of hospitalized patients with Covid 19 and their interpretations, as well as the behavior of the main variables of the research through tables, graphs and relevant statistical measures. All the proposed varia-bles were analyzed using the logistic regression method, based on modeling with attempted estimates of several alternatives of predictor variables, seeking to better explain the patient's outcome. The analysis presented here will provide an overview of the Pandemic and the deter-mining factors in this process. The results showed the characterization of patients hospitalized in the period under study at the Regional Hospital of Cajazeiras in the Alto Sertão of Paraíba, through the modeling of the study, we identified that the only variable that was significant at the level α = 0.05 for the data available for the year 2020 and 2021 was the age variable, the estimated model also pointed out that the greater the patient's age, the greater the chances of the patient dying, with regard to the outcome. It is also important to highlight that studies of this nature can help and support health professionals responsible for managing health institutions that need reliable information to guide the planning of public health policies and necessary interventions, in the face of situations such as the Covid-19 pandemic.